Discourse Analysis: Textual Function In Oprah Winfrey - Rani Rakasiwi (Jurnal Scientia, 2021)
This study deals with Theme and Rheme in Oprah Winfrey. The objectives of the research were to find out the most dominant type of theme used in Oprah Winfrey. The tweets in Oprah Winfrey around 38 tweets used as the source of data in this research. This research was performed by using the descriptive qualitative method. The technique for analyzing data were copying all the content in Ms. Word to be printed out, separating each sayings to be analyzed based on the data and time, analyzing every sentence in the column of the sayings based on the types of theme, classifying the theme based on the type of Simple Theme, calculating the percentage of each theme, finding out the dominant type of theme in Oprah Winfrey. The findings indicated that Simple Theme there were 89.85% of Theme (Unmarked) and 10.15% of Theme (Marked). It means that the dominant type of Simple Theme in Oprah Winfrey was Theme (Unmarked) that was 89.85%.